Effect of stress corrosion and bone regeneration on in vivo cavity in clinical osteonecrosis treatment with high-purity magnesium screws - Leyao Zhang; Yijin Zhang; Jiahao Sun; Shengyu Duan; Zeang Zhao; Panding Wang; Jirong Shen; Hongshuai Lei (Materials & Design)
High-purity magnesium (HP Mg) is a biodegradable metallic material, that could be applicated in implants treating osteonecrosis of the femoral head and treating peripheral artery disease. However, the degradation behavior of Mg implants was studied previously using in-vitro or in-vivo in the subcutaneous environment of rats or rabbits. This work conducted a clinical experiment on the treatment of femoral head necrosis with Ti and degradable HP Mg implants to evaluate their efficacy in enhancing surgical outcomes. During the 12-month follow-up after surgery, treatment outcomes in patients were assessed by CT, DCE-MRI and Harris hip score (HHS). The inconsistency of HP Mg degradation and bone regeneration rate induced cavities in human bodies. The effects of stress on in vitro and in vivo corrosion of Mg during implantation were investigated using experiment tests and finite element analysis. HP Mg can improve surgical effects compared to Ti in clinical applications. However, stress accelerated the corrosion of HP Mg and increased hydrogen released volume, inducing tissue and bone cavities. Stress concentration arising from cavities in adjacent bone tissue triggered localized bone density elevation and influenced osseointegration. These findings provide valuable insights into the in vivo degradation mechanisms of HP Mg in clinical applications.